2008
DOI: 10.1007/s00125-008-1071-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of N ε-(3-formyl-3,4-dehydropiperidino)lysine as a novel biomarker for the severity of diabetic retinopathy

Abstract: Aims/hypothesis Recent studies suggest that oxidative stress should be monitored alongside HbA 1c to identify subgroups of diabetic patients at high risk of initiation or progression of retinopathy. The acrolein-derived advanced lipoxidation end-product (ALE), N " -(3-formyl-3,4-dehydropiperidino)lysine (FDP-lysine), is a useful biomarker that reflects the cumulative burden of oxidative stress over long periods of time. The purpose of the present study was to investigate whether serum and haemoglobin levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…One study by Losado et al reported that concentrations of the ALE precursor, MDA, are elevated in type 1 patients with retinopathy when compared to diabetics without retinopathy and healthy controls [45]. More recently, we have demonstrated that haemoglobin levels of the ACR-derived ALE, FDPlysine, are associated with the severity of diabetic retinopathy in type 1 and type 2 diabetic patients [88]. Importantly, the relationship of FDP-lysine with retinopathy was unaltered after adjustment for HbA1c, or other clinical parameters.…”
Section: Clinical Correlates With Diabetic Retinopathysupporting
confidence: 48%
See 2 more Smart Citations
“…One study by Losado et al reported that concentrations of the ALE precursor, MDA, are elevated in type 1 patients with retinopathy when compared to diabetics without retinopathy and healthy controls [45]. More recently, we have demonstrated that haemoglobin levels of the ACR-derived ALE, FDPlysine, are associated with the severity of diabetic retinopathy in type 1 and type 2 diabetic patients [88]. Importantly, the relationship of FDP-lysine with retinopathy was unaltered after adjustment for HbA1c, or other clinical parameters.…”
Section: Clinical Correlates With Diabetic Retinopathysupporting
confidence: 48%
“…Lipid peroxidation is enhanced in diabetes, and diabetic patients have higher serum levels of MDA than non-diabetic subjects [30]. It has also been reported by our own group and others that FDP-lysine-and HNE-modified proteins accumulate in serum of patients with diabetes compared to control individuals [74,88]. At present, however, our understanding of the role of ALEs in the pathogenesis of diabetic complications, particularly retinopathy, lags far behind that which is currently known about AGEs.…”
Section: Biochemistry Of Age and Ale Formationmentioning
confidence: 78%
See 1 more Smart Citation
“…Dark grey bars, pyridoxamine-treated diabetic; light grey bars, diabetic; black bars, non-diabetic. ***p<0.001 vs NonDb; † † p< 0.01 vs Db levels of the acrolein-derived FDP-lysine are associated with severity of retinopathy in type 1 and type 2 diabetic patients [34].…”
Section: Discussionmentioning
confidence: 98%
“…Increased levels of hemoglobin FDP-Lys have been associated with the severity of diabetic retinopathy in type 1 and type 2 diabetic patients, and its formation is involved in the pathogenesis of this sight-threatening complication of diabetes [71].…”
Section: Ex Vivo-in Vivo Studiesmentioning
confidence: 99%